2019
DOI: 10.1097/brs.0000000000002971
|View full text |Cite
|
Sign up to set email alerts
|

Mineralized Collagen Modified Polymethyl Methacrylate Bone Cement for Osteoporotic Compression Vertebral Fracture at 1-Year Follow-up

Abstract: Study Design. Retrospective comparative study. Objective. This study aimed to compare the clinical effects and imaging features of polymethyl methacrylate (PMMA) bone cement with and without mineralized collagen (MC) in percutaneous kyphoplasty (PKP) for osteoporotic vertebral compression fractures (OVCFs). Summary of Background Data. PKP with PMMA is widely performed for OVCF. However, numerous complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Both PKP and PVP are safe and effective surgical procedures for treating OVCFs [ 29 ]. However, in terms of restoring vertebral height and local kyphotic corrections, PKP is relatively better than PVP [ 30 ]. Studies of PKP have indicated that the procedure duration of PKP is short and this technique yields fewer cement leakages with better pain relief, improvements of ODI, and a trend towards a longer fracture-free survival [ 31 , 32 ].…”
Section: The Development Of Vertebral Augmentation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PKP and PVP are safe and effective surgical procedures for treating OVCFs [ 29 ]. However, in terms of restoring vertebral height and local kyphotic corrections, PKP is relatively better than PVP [ 30 ]. Studies of PKP have indicated that the procedure duration of PKP is short and this technique yields fewer cement leakages with better pain relief, improvements of ODI, and a trend towards a longer fracture-free survival [ 31 , 32 ].…”
Section: The Development Of Vertebral Augmentation Systemsmentioning
confidence: 99%
“…Currently, mineralized collagen-modified PMMA (MC-modified PMMA), a kind of new bone cement that does not change the beneficial properties of PMMA, has better biocompatibility than normal PMMA. It has been reported that this new bone cement forms a stable structure in the vertebral body as well as improves the prognosis of patients who have OVCFs by reducing pain and reoperation [ 30 ]. With the development of biomaterials, it is possible to obtain new types of bone cement with bioactivity, excellent biomechanics, and even osteogenesis and appropriate degeneration.…”
Section: The Development Of Vertebral Augmentation Systemsmentioning
confidence: 99%
“…However conservative treatment is usually not effective in relieving symptoms. PVP and PKP are highly effective in relieving pain and improve the prognosis of OVCF 20,21 . They have advantages including vertebral body formation, minimally invasive, rapid pain relief, quick recovery, and have been widely used in the treatment of OVCF.…”
Section: Clinical Research Progress Of Pvp In Treatment Of Ovcf and Cmentioning
confidence: 99%
“…[28][29][30] Via the modification, bone formation at the interface between the bone cement and host bone could be observed, and secondary fracture was significantly decreased as shown by longterm follow-ups. [31][32][33] Although MC-modified PMMA bone cement has many advantages compared with traditional bone cement, it has not been used for interbody fusion. Moreover, an appropriate biomaterial and applicable operative method need to be developed.…”
Section: Introductionmentioning
confidence: 99%